When music goes to school : perspectives on learning and teaching - Littleton, Danette, 1942- (Lanham : Rowman & Littlefield, 2015)
"Experts in child psychology and pedagogy concur that how children are schooled today seriously conflicts with how they learn and develop. Children are being left behind and the promises and possibilities of childhood are slipping away. This book aims to disclose a deeper understanding of music's importance in children's lives and their need to know, explore, wonder, and play. Directed toward music teachers, teacher educators, and scholars, this text invites inquiries and provides insights into contemporary challenges to learning and teaching in an era of standardization. A compendium of essays, classroom voices and vignettes is supported by relevant research in music education and companion disciplines in psychology, philosophy, and sociology. Storytelling with scholarship contributes authenticity and strengthens the premise of this book." -- Publisher's description.
Acknowledgments -- Prologue: A Child's Mind Is a Terrible Thing to Standardize -- Introduction: Toward Individualism, Imagination, and Inventiveness -- 1. Individualism: A Curriculum of One -- 2. Imagination: The Musical Culture of Children's Play -- 3. Originality: The Voices of Children -- 4. Inventiveness: Making Meaningful Music with Children -- 5. Perspectives: Voices of Teachers -- Epilogue: On the Cusp of Possibility -- Postscript -- Bibliography -- Works Cited -- Index
Includes bibliographical references (pages 131-133) and index.
Keywords: School music -- Instruction and study